Microcomputer programs for the identification of rural service centers : evaluation of field data from Jambusar Block, Gujarat State, India - Mehta, Barjor Erach; Kammeier, Hans Detlef; Weber, Karl E.; Radok, Rainer; Governments of New Zealand and Canada (Bangkok : Asian Institute of Technology, 1983)
The search for 'from below' planning procedures has led to the emergence of sub regional plans. In India, these plans have been labelled as 'Block Level Plans'. An important component of such plans has been the identification of Service Centers and the lack of infrastructural services in those regions. The time consuming construction of a scalogram or Guttman Scale has for long been advocated as an appropriate tool for such planning. This study presents microcomputer programs written in the BASIC language for scalogram construction so as to hasten the construction process and increase the number of possibilities for its use. Primary data collected from Jambusar Block of Gujarat State, Western India, during the period May-June 1983 is utilized to illustrate the use of the microcomputer programs. The study states the limitations of the scalogram as a tool and finally points at another tool which needs to be developed to supplement the scalogram, i.e. programs for the analysis of clusters of villages using the services available at different rural centers.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Science, School of Engineering and Technology
Thesis (M.Sc.) - Asian Institute of Technology, 1983
Keywords: Social service, Rural -- India -- Jambusar Block; Social service, Rural -- Computer programs